2022
DOI: 10.3389/fdgth.2022.909294
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of a dashboard prototype for real-time suicide mortality data

Abstract: Introduction/AimData visualisation is key to informing data-driven decision-making, yet this is an underexplored area of suicide surveillance. By way of enhancing a real-time suicide surveillance system model, an interactive dashboard prototype has been developed to facilitate emerging cluster detection, risk profiling and trend observation, as well as to establish a formal data sharing connection with key stakeholders via an intuitive interface.Materials and MethodsIndividual-level demographic and circumstant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The complexity of the task could partially explain the slow uptake in the use of real-time data to detect suicide clusters. The exception to this is the work by Benson and colleagues, who have used the scan statistic as the basis for prospective monitoring of suicide clusters in Cork County, Ireland (Benson et al, 2022). They developed a prototype real-time cluster surveillance system that presented summary results for dissemination in a way that supports decision-making in suicide prevention.…”
Section: Can We Use Registers To Detect Suicide Clusters?mentioning
confidence: 99%
“…The complexity of the task could partially explain the slow uptake in the use of real-time data to detect suicide clusters. The exception to this is the work by Benson and colleagues, who have used the scan statistic as the basis for prospective monitoring of suicide clusters in Cork County, Ireland (Benson et al, 2022). They developed a prototype real-time cluster surveillance system that presented summary results for dissemination in a way that supports decision-making in suicide prevention.…”
Section: Can We Use Registers To Detect Suicide Clusters?mentioning
confidence: 99%
“…Real-time monitoring systems can also enable public health agencies and policy-makers to identify new trends, such as locations or populations of concern 17 18. For example, real-time monitoring in Japan during the COVID-19 pandemic identified that, after an initial decline in suicides, the numbers started to rise, particularly among young women,19 enabling a swift and targeted policy response 1.…”
Section: Introductionmentioning
confidence: 99%